The Effect of Puzzle Educational Game Tools on Fine Motor Development in Pre-school Children at Al-Wahdah Kindergarten Bandung City - Divta Safira, Riska; Lukitasari, Depi; Nurlita, Lita (LPPM STIKes Muhammadiyah Ciamis, 2023)
Fine motor development is a movement that uses smooth muscles or certain parts of the body that are influenced by learning and practicing opportunities. Delayed fine motor development results in children's development being inappropriate for their age. Overcoming this, need stimulation to improve fine motor skills such as playing a puzzle. The purpose of this study was to determine the effect of Educational Games Tools puzzle on fine motor development in children. This type of research is pre-experimental research with one group pre-test post-test design. The sample of this study was children aged 5-6 years in TK Al-Wahdah totaling 45 samples. The instrument of this research used a modified sheet of KPSP fine motor. Analysis of univariate data before being treated to playing puzzles, found that there were 33 children in the appropriate category (73.3%) and 12 people in the unsuitable category (26.7%). After being given therapy playing puzzle children in the appropriate category were 45 people (100.0%). Based on the results of calculations using the Mc Nemar test, a p-value of 0.000 < (0.05) was obtained, and X counted 14.08 >X table 3.841. It can be concluded that there is an effect of puzzle educational game tools on fine motor development in pre-school age children at TK Al-Wahdah Bandung City. For teachers and health centers it is recommended to be able to redevelop puzzle games by stimulating children to use puzzles that are more varied and harmless, and can pay more attention to fine motor development in children in the future.